Prevalence of extrapulmonary tuberculosis among people living with HIV/AIDS in sub-Saharan Africa: a systemic review and meta-analysis - Mohammed, Hussen (HIV AIDS (Auckl), 2018)
BACKGROUND: The double burden of infectious diseases such as tuberculosis (TB) and HIV disproportionately affects Africa. Our objective was to summarize the prevalence of extrapulmonary TB (EPTB) among people living with HIV/AIDS (PLWHA) in sub-Saharan Africa (SSA). METHODS: We searched PubMed and Google Scholar for studies done on the prevalence of EPTB among PLWHA which published in English from 1990 to 2017. We also searched bibliographic indices and browsed through reference lists of articles and journals. We critically appraised the quality of articles and abstracted the data with Joanna Briggs Institute (JBI) checklists. We used Review Manager Software (version 5.3) and Compressive Meta-analysis Software (version 2.2) for analysis. Finally, we summarized the effect estimate by using random-effects model and explored potential sources of heterogeneity by subgroup and sensitivity analyses. We assessed publication bias by funnel plot and statistical test. Finally, we used PRISMA format for reporting. RESULTS: We included, in this review, 31 studies that fulfilled our inclusion criteria, with a total population of 28,659. The prevalence estimate of EPTB among PLWHA ranged from 6.4% (95% CI: 3.8, 9.0) to 36.8% (95% CI: 28.6, 45); random-effects pooled prevalence of EPTB among PLWHA was found to be 20% (95% CI: 17, 22; heterogeneity: τ(2)=0; χ(2)=509.09, degrees of freedom [df]=30, P<0.00001; I(2)=94%). No evidence of publication bias was observed (P=0.44 for Egger’s regression analysis and P=0.11 for Begg’s rank correlation analysis). CONCLUSION: We can conclude from our analyses that the prevalence of EPTB among PLWHA was high. It is necessary to give emphasis for EPTB, especially when screening TB among PLWHA, widening the spectrum of screening to include all EPTB sites in the countries with high EPTB and/or HIV prevalence in the general population.